Infant respiratory sinus arrhythmia and maternal depressive symptoms predict toddler sleep problems. Issue 2 (18th October 2016) - Gueron‐Sela, Noa; Propper, Cathi B.; Wagner, Nicholas J.; Camerota, Marie; Tully, Kristin P.; Moore, Ginger A.
Abstract: This study examined the direct and interactive effects of infants' respiratory sinus arrhythmia (RSA) and maternal depressive symptoms (MDS) during the first 6 months of life in the prediction of children's sleep problems at age 18 months. Participants included 156 children and their mothers who were followed from 3 to 18 months of age. At ages 3 and 6 months, infants' cardiac activity was recorded at rest and during the still‐face paradigm, a mother–child social challenge task, and estimates of infant baseline RSA (RSAB) and RSA withdrawal (RSAW) were calculated. Mothers reported about their depressive symptoms at 3, 6, and 18 months, and about infants' sleep problems at age 18 months. Less RSAW and higher levels of MDS predicted more sleep problems at age 18 months. Additionally, RSAB moderated the link between MDS and children's sleep problems such that MDS were related to more sleep problems only for infants with high levels of RSAB. Results illustrate the importance of RSA as both a direct predictor and a moderator of maternal influences in the prediction of early sleep problems.